New Evidence on Ethnic Diversity and Social Capital in Indonesia - Sanjaya, Muhammad Ryan (Jurnal Ekonomi & Studi Pembangunan, 2022)
This study analyzes the relationship between the various measures of ethnic diversity and social capital in Indonesia, particularly trust and tolerance (towards other religions and other ethnic groups), using a nationally representative survey. The 2009 National Socioeconomic Survey asked almost 300 thousand individuals on social capital from the 2010 population census data used to construct measures of ethnic and religious diversity. The study’s main contribution to the literature is the inclusion of ethnic similarities in the construction of these diversity variables using linguistic tree data taken from Ethnologue. Using the multiple linear regression method, the study found that all measures of diversity are negatively associated with trust but are positively associated with tolerance, even after controlling for individual-, household- and district-level characteristics. Anticipating the possibility of endogeneity in the diversity variables, this study uses geographical variables to instrument these variables. Nevertheless, the use of the instrumental variable regression method does not change the main result.